Eligibility Multimedia Interactive Language Skills Learning for Primary School Teacher Education - Ebi Praheto, Biya; ., Andayani; Rohmadi, Muhammad; Eko Wardani, Nugraheni (International Journal of Engineering and Technology, 2018)
This study aims to determine the eligibility of interactive multimedia for Indonesian language skills courses in Primary School Teacher Education Study Program. This study is part of the development research at the limited trial stage. This research was conducted in university Sarjanawiyata Tamansiswa in the even semester of the academic year 2017/2018. The object of this research is the students who taught the subjects of Indonesian language skills, lecturers of Indonesian language skills courses, media experts and material experts. Based on the results of eligibility assessment from the expert, material expert, media experts, and users both lecturers and students can be seen that interactive multimedia skills in Indonesian language is declared eligible with the good category. The results of the assessment are media experts with a score of 3.38 percentages 67.63%, material expert score 4.41 percentage 88.14%, lecturer score 4.25 percentages 85% and students 4.42 percentages 88.43%. The average eligibility score of 4.12 with 82.3% percentages is in very good category.Â